2021
DOI: 10.3390/biomedicines9040362
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole Exhibits Anti-Neoplastic Actions against Gastric Cancer Cells by Affecting STAT3 and STAT5 Activation by Pleiotropic Mechanism(s)

Abstract: Albendazole (ABZ) has been reported to display anti-tumoral actions against various maliganncies, but possible impact of ABZ on gastric cancer has not been deciphered. As aberrant phosphorylation of STAT3 and STAT5 proteins can regulate the growth and progression of gastric cancer, we postulated that ABZ may interrupt the activation of these oncogenic transcription factors. We found that ABZ exposure abrogated STAT3/5 activation, inhibited phosphorylation of Janus-activated kinases 1/2 and Src and enhanced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Ehteda et al found that the combination of ALB with 2-methoxyestradiol synergizes the induction of apoptosis of colon cancer cells and improves the survival of HCT-116 tumor-bearing nude mice [ 47 ]. The synergy was based on the sum effect of microtubule-binding activity of both drugs, which differs from our approach, which is based on the possible sum of the different mechanisms of action attributed to ALB and MLT, as mentioned above [ 17 , 18 , 24 , 27 ]. On the other hand, MLT also has shown a chemosensitizing effect, since MLT downregulates the expression of ABC transporter ABCG2, inducing the synergistic cytotoxicity when combined with TMZ against GB cells and GB-stem cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ehteda et al found that the combination of ALB with 2-methoxyestradiol synergizes the induction of apoptosis of colon cancer cells and improves the survival of HCT-116 tumor-bearing nude mice [ 47 ]. The synergy was based on the sum effect of microtubule-binding activity of both drugs, which differs from our approach, which is based on the possible sum of the different mechanisms of action attributed to ALB and MLT, as mentioned above [ 17 , 18 , 24 , 27 ]. On the other hand, MLT also has shown a chemosensitizing effect, since MLT downregulates the expression of ABC transporter ABCG2, inducing the synergistic cytotoxicity when combined with TMZ against GB cells and GB-stem cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALB and ALBSO are classically known for their affinity for tubulin and alteration of the microtubule assembly [ 16 ]. In addition, ALB has been reported is pleiotropic drugs with multiple effects on cells, including the inhibition of phosphorylation signaling pathways [ 17 ] and induction of oxidative stress promoting DNA fragmentation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…HCCLM3 and HepG2 cells were pre-treated with DA (0, 20, 40, 60, and 80 µM) for 2 h and then exposed to HGF (50 ng/mL) for a total of 48 h. The viability of cells was determined through the MTT assay, as described earlier [52]. In brief, the cells were grown in a 96-well plate and incubated with DA for the indicated time at the indicated concentrations.…”
Section: Mtt Assaymentioning
confidence: 99%
“…In Ehrlich carcinoma model in mice, albendazole induced oxidative stress promoting DNA fragmentation, triggering apoptosis, and inducing cancer cell death [ 33 ]. Further, albendazole exerted its anti-cancer activity in gastric cancer cell lines by disrupting microtubule formation and function to cause mitotic arrest and inducing cancer cell apoptosis [ 353 ] or by affecting STAT3 and STAT5 activation by pleiotropic mechanisms [ 354 ]. However, the anti-tumor activity of albendazole was cancer cell-type dependent; 13 of 14 human papillomavirus-negative head and neck squamous cell cancer cell lines responded well to albendazole, whereas only 3 of 6 human papillomavirus-positive head and neck squamous cell cancer cell lines responded to albendazole [ 355 ].…”
Section: Anti-cancer Effectsmentioning
confidence: 99%